New results on bound excitons in quantum wells - Oliveira, José Brás Barreto de [UNESP]; Meneses, E. A.; Da Silva, E. C F (My University, 1997)
The formation of bound excitons (BE) is investigated for a GaAs/GaAlAs multiple quantum well (QW) system. The photoluminescence (PL) spectra are analysed as a function of the excitation energy. It was found that the carriers photogeneration, either in the barrier or directly in the well, do not play an important role on the BE formation. We conclude that defects localized at interfaces are ionized by of capture charges which in turn bound the free exciton (FE).